EFFECTIVENESS OF USING PAPAYA SEED EXTRACT (Carica papaya L.) AS A GONAD MATURITY INHIBITOR FOR NILE TILAPIA (Oreochromis niloticus) - Halil Halil; Damis Damis; Surianti Surianti (Universitas Mataram, 2026)
One of the rapidly growing cultivation businesses in the Sidenreng Rappang Regency is tilapia cultivation, but in the cultivation process of tilapia commodities, problems are often found, including stunted growth, relatively long harvest times, and large amounts of feed consumption, which increase the number of losses during cultivation. In other words, tilapia is a type of commodity that has a fast fertilization process, so an alternative material is needed to determine good gonads in the growth and survival of tilapia, so the alternative material used is papaya seed extract. This study aims to determine and study the dosage of papaya seed extract used to see the level of gonad maturity, growth, and survival of female tilapia. This study will be conducted from February to May 2025, located at Jl. Ahmad Taufik, Panca Rijang District, Sidenreng Rappang Regency, South Sulawesi, Indonesia. The study used 4 treatments, namely treatment A. Commercial feed 100 gr + Papaya seed extract 0 ml / kg feed (100% feed), in treatment B. Commercial feed 100 gr + Papaya seed extract 0.1 ml / kg feed, while treatment C. Commercial feed 100 gr + Papaya seed extract 0.2 ml / kg feed, and treatment D. Commercial feed 100 gr + Papaya seed extract 0.3 ml / kg feed, with 3 repetitions. Data analysis used Analysis of Variance (ANOVA) and a simple analysis was carried out in looking at primary metabolites in the liquid.